2018
DOI: 10.1038/s41598-018-32263-y
|View full text |Cite
|
Sign up to set email alerts
|

Divergent action of fluoxetine in zebrafish according to responsivity to novelty

Abstract: Here we show that the novel object recognition test can discriminate between high (HRN, neophobic) and low (LRN, neophilic) novelty responders in zebrafish populations. Especially when we observe the latency to the first entry in the novel object zone, zebrafish did not maintain these behavioral phenotypes in sequential tests and only the HRN group returned to their initial responsive behavior when exposed to fluoxetine. Our results have important implications for behavioral data analysis since such behavioral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…Urocortin 3 stimulates behaviors associated with anxiety reduction (Venihaki et al, 2004) and prolactin has a role in regulating neuroendocrine responses to stress in the brain, as well as a protective role against stress-induced damage through immunoenhancement (Lennartsson and Jonsdottir, 2011;Torner and Neumann, 2002). However, other studies, using adult and juvenile D. rerio and adult females of G. holbrooki, testing concentrations from 0.005 to 100 μg/L and different exposure periods (from 30 min to 43 days), reported no effect on stressassociated behavior (Fontana et al, 2022;Petrunich-Rutherford, 2019) or an anxiogenic effect with lower swimming distances at the top of the aquarium, as well as increased freezing periods (Fior et al, 2018;Giacomini et al, 2020;Marcon et al, 2016;Meijide et al, 2018;Orozco-Hernández et al, 2022b).…”
Section: Locomotor Behaviormentioning
confidence: 98%
“…Urocortin 3 stimulates behaviors associated with anxiety reduction (Venihaki et al, 2004) and prolactin has a role in regulating neuroendocrine responses to stress in the brain, as well as a protective role against stress-induced damage through immunoenhancement (Lennartsson and Jonsdottir, 2011;Torner and Neumann, 2002). However, other studies, using adult and juvenile D. rerio and adult females of G. holbrooki, testing concentrations from 0.005 to 100 μg/L and different exposure periods (from 30 min to 43 days), reported no effect on stressassociated behavior (Fontana et al, 2022;Petrunich-Rutherford, 2019) or an anxiogenic effect with lower swimming distances at the top of the aquarium, as well as increased freezing periods (Fior et al, 2018;Giacomini et al, 2020;Marcon et al, 2016;Meijide et al, 2018;Orozco-Hernández et al, 2022b).…”
Section: Locomotor Behaviormentioning
confidence: 98%
“…Zebrafish provide an important perspective for drug screening for depression. Recent studies have successfully applied CUMS to zebrafish to explore depression-like states and changes to the brain proteome profile and neurogenesis, the results showed memory deficits and elevated cortisol levels caused by CUMS, which are similar to depression-like states in humans and rodents [18][19][20]. It has been reported that after the stress with reserpine, the locomotor ability and exploratory behavior of zebrafish were reduced, the levels of cortisol were increased, and 5-HT and norepinephrine were decreased [21], which also simulated the state of human depression.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of differential responses to SSRI depending on personality in fish are few. Fior et al (2018) found that shier and bolder zebrafish differed in their response to fluoxetine as measured by a novel object test. LePage et al (2005) found that citalopram reduced aggression in rainbow trout but only for individuals with experience of being dominant.…”
Section: Discussionmentioning
confidence: 97%
“…Correlations between multiple behavioural traits are known as behavioural syndromes (Huntingford 1976;Bell and Stamps 2004;Bell 2005;Carter et al 2013). Recent studies indicate that proactive and reactive fish can respond differently to SSRI treatment (Fior et al 2018).…”
mentioning
confidence: 99%